PENTINGNYA MEMAHAMI ATURAN KHUSUS MENGENAI WAJIB PAJAK DI INDONESIA - Indriani, Vena Quin (Universitas Pembangunan Panca Budi, 2023)
Taxpayers are individuals or entities that have the authority to pay taxes, withhold taxes, and collect taxes, and have rights and obligations related to taxation in accordance with the provisions in force in Indonesia. One of the things that are related or identical with taxpayers is the Taxpayer Identification Number (NPWP), so every individual has an NPWP in carrying out his tax rights and obligations. As a good citizen, you must comply with tax rules in accordance with the law (UU) on taxation, because the effect of taxes is very influential on the economic balance in Indonesia as well as having a taxpayer is proof that a country can definitely improve the country's economy because taxes can be used as a tool to optimally enter funds into the State treasury so that it finances the expenditure of the State's own interests. If citizens are educated & understand about the special rules of taxation, it cannot be denied that the potential for state revenues will increase and will return or have an impact on the community. Therefore, it is important to understand the special rules regarding the obligations of Indonesian citizens to pay taxes.